Delimitation of Molecular Operational Taxonomic Units (MOTU) and euglossine bees diversity in two altitudinal gradients of northern Colombia - Rodríguez-Serrano, Juanita; Prieto, Carlos; Balke, Michael (Revista Colombiana de Entomología, 2025)
The tribe Euglossini (orchid bees) is vital for tropical pollination, making their diversity and distribution across altitudinal gradients crucial for ecological studies and conservation. This study assesses Euglossini diversity in northern Colombia’s Sierra Nevada de Santa Marta and Serranía del Perijá, focusing on altitudes from 600 to 2200 meters above sea level (m a.s.l.). Using Barcode Index Numbers (BIN) and the COI gene, 1258 male specimens were collected, with 415 individuals sequenced. We identified 21 Molecular Operational Taxonomic Units (MOTUs), from which BOLD: AEF4646 (Eufriesea) was identified as the most variable, BOLD: AEF4645 (Eufriesea) as the most divergent molecular species, and also species like BOLD: AAC0547 (Euglossa) are widely distributed in both SNSM and SP at 800 and 1000 m a.s.l., while BOLD: AAC3172 (Euglossa) is strongly associated with 800 m a.s.l. communities. Additionally, BOLD: ABY5852 (Euglossa) prefers sites between 1400 m and 1800 m a.s.l. Diversity analyses revealed no significant differences in species richness between the gradients, but richness declined with altitude. Eufriesea and Euglossa species were broadly distributed in the Sierra Nevada, while Euglossa and Eulaema dominated the Serranía del Perijá. Beta diversity analyses showed distinct distribution patterns, with intermediate elevations marking a transition zone. Above 2000 m a.s.l., evolutionary processes likely sustain Euglossini populations, emphasizing the role of these regions in bee diversification.